State mandates on renewable heating technologies and the housing market - Robert Germeshausen; Kathrine von Graevenitz (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We study the effect of a state level mandate on renewable heating technologies on the housing market. The mandate requires a minimum share of 10 % renewable energy sources when changing the heating system in the existing building stock. As renewable energy sources are still more expensive than conventional alternatives this mandate could lower the relative price of homes in the existing building stock when a replacement of the heating system is impending. We implement a two stage difference-in-differences nearest neighbor matching approach to identify the effect on prices taking advantage of differences in regulation by location and vintage of the building stock. Our results find no evidence of an effect of the mandate on housing prices.
Keywords: Q42; Q48; Q58; 330; Building regulations; Renewable energy sources; Hedonic pricing